Occurrence of Morphological and Anatomical Adaptive Traits in Young and Adult Plants of the Rare Mediterranean Cliff Species Primula palinuri Petagna. (30th April 2012) - De Micco, Veronica; Aronne, Giovanna
Abstract : Cliffs worldwide are known to be reservoirs of relict biodiversity. Despite the presence of harsh abiotic conditions, large endemic floras live in such environments. Primula palinuri Petagna is a rare endemic plant species, surviving on cliff sites along a few kilometres of the Tyrrhenian coast in southern Italy. This species is declared at risk of extinction due to human impact on the coastal areas in question. Population surveys have shown that most of the plants are old individuals, while seedlings and plants at early stages of development are rare. We followed the growth of P. palinuri plants from seed germination to the adult phase and analysed the morphoanatomical traits of plants at all stages of development. Our results showed that the pressure of cliff environmental factors has been selected for seasonal habitus and structural adaptive traits in this species. The main morphoanatomical modifications are suberized cell layers and accumulation of phenolic compounds in cell structures. These features are strictly related to regulation of water uptake and storage as well as defence from predation. However, we found them well established only in adult plants and not in juvenile individuals. These findings contribute to explain the rare recruitment of the present relict populations, identifying some of the biological traits which result in species vulnerability.